Combined step potential electrochemical spectroscopy and electrochemical impedance spectroscopy analysis of the glassy carbon electrode in an aqueous electrolyte. (10th November 2021) - Davey, Sofia B.; Cameron, Amanda P.; Latham, Kenneth G.; Donne, Scott W.
Abstract: The nature of the electrified interface between a planar non-porous glassy carbon electrode and an aqueous electrolyte of 0.5 M Na2 SO4 is examined using the combination of step potential electrochemical spectroscopy (SPECS) and electrochemical impedance spectroscopy (EIS) across the full potential window of stability. This combination of techniques provides insight into the dynamics of interface formation (SPECS), as well as interfacial structure (EIS), highlighting the variation in capacitance across the potential window. EIS frequency also plays a significant role in determining capacitance via the role that it plays in determining ionic and dipole movement. High frequencies stimulate electron cloud movement, followed by dipole rotation and ionic movement as the frequency progressively decreases. Outcomes further highlight the role that mass transport has on the amount of charge storage at the interface.